Incidence, risk factors, and therapeutic management of equine colic in Lamongan, Indonesia - Faisal Fikri; Dodit Hendrawan; Arya Pradana Wicaksono; Agus Purnomo; Shafia Khairani; Shekhar Chhetri; Salipudin Tasil Maslamama; Muhammad Thohawi Elziyad Purnama (Veterinary World, 2023)
Background and Aim: Colic is among the common health issues in equine health management. Gastrointestinal (GI) disorders are the most frequent causes of colic, but dysfunction of other organs and systems inside the abdominal cavity may also contribute. Therefore, it is crucial to identify risk factors for colic of specific etiologies. This study aimed to examine the incidence, risk factors, and best therapeutic management practices for horses with colic.